(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
The aim of this study was to investigate the factors affecting the promotion of entrepreneurship that based on personality traits of managers and staff of the Ministry of the Education, the population consists of all managers of the ministry of education that the number of 157 people of which 113 were selected as statistical sample, standard entrepreneurship questionnaire was used to collect data. To determine its validity and faculty supervisor and consultant enjoyed. In order to assess the reliability of the test, 35 copies of questionnaires were distributed among respondents; the Cronbach’s alpha coefficient was 0.75 after collecting the questionnaires and entering into SPSS software. Results from this study indicate that questions based on the promotion of entrepreneurial personality characteristics and problem-solving ability, there is significant direct relationship.